The Rare Face of an Infrequent Lymphoma Diagnosed by an Exquisite Method: Case Report with Review of Literature - Lali, Bhagat S.; Dey, Debdeep; Bhave, Saurabh J.; Parihar, Mayur; Lingegowda, Dayanand; Das, Jayanta; Chatterjee, Suvadip (Indian Journal of Medical and Paediatric Oncology, 2021)
Large B-cell lymphomas include both the commonly encountered, as well as not so frequent entities. We report a rare case of hepatic intravascular large B-cell lymphoma (IVLBCL). These cases usually pose a major challenge to timely diagnosis due to the limited clinical exposure and nonspecific symptoms; however, timely diagnosis is possible with awareness of this entity and close coordination between radiology and pathology. The patient presented with pain abdomen, fever, edema, hepatomegaly but no lymphadenopathy or cutaneous lesions were identified. Blood investigations revealed pancytopenia, high lactate dehydrogenase (LDH) levels and bone marrow investigations were not helpful. Left-sided portal hypertension, coagulopathy, and hypoalbuminemia raised a clinical suspicion of chronic liver disease with high LDH levels and liver biopsy was challenging in view of very low platelet counts. The uniquely explored transjugular biopsy helped in obtaining liver tissue which showed sinusoidal large atypical lymphoid cells positive for CD20 rendering a diagnosis of IVLBCL. After administration of the R-miniCHOP chemotherapy, there was evident clinical and radiological response. This case highlights the importance of considering transjugular liver biopsy in scenarios where the clinical presentation is unusual. At the same time, a meticulous histological examination is needed to diagnose a rare yet potentially treatable large B cell lymphoma.
Keywords: lymphoma; intravascular; transjugular liver biopsy; challenging; rituximab